Mental health and debt collection: a story of progress? Exploring changes in debt collectors' attitudes and practices when working with customers with mental health problems, 2010–2016. (2nd November 2018) - Evans, Jamie; Fitch, Christopher; Collard, Sharon; Henderson, Claire
Abstract: Background : In recent years, the UK debt collection industry has taken steps to improve its policies and practices in relation to customers with mental health problems. Little data, however, have been collected to evidence change. Aims : This paper examines whether the reported attitudes and practices of debt collection staff when working with customers with mental health problems have changed between 2010 and 2016. Method : This paper draws on descriptive and regression analyses of two cross-sectional surveys of debt collection staff: one conducted in 2010 and one conducted in 2016. Results : All variables analysed show statistically significant changes between 2010 and 2016 indicative of improved reported attitudes and practices. Conclusions : While results suggest an improvement in attitudes and practice may have occurred between 2010 and 2016, research is required to understand this potential shift, its likely causes, and concrete impact on customers.